Pengaruh Customer Experience, Ease of Use, dan Customer Trust Terhadap Repurchase Intention Konsumen Situs Jual Beli Online Shopee - Mariati Tirta Wiyata; Elisya Pramana Putri; Ce Gunawan (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2020)
The purpose of this study is to determine the effect of Customer Experience, Ease of Use, and Customer Trust, on Consumer Repurchase Intention of Online Shopee Sale and Purchase Sites among Sukabumi City College Students. Methodology: The research method used was a survey method using a questionnaire distributed to 100 samples. While the instrument quality testing techniques include validity and reliability tests. The classic assumption test technique uses the normality test, multicollinearity test, and heteroscedasticity test. As for testing the hypothesis using multiple linear regression analysis, t test (partial), and f test (simultaneous). Results: That three of the five Customer Experience variables namely Sense (Sensory Experience), Think (Cognitive Experience), and Act (Physical Experience) have no effect on Repurchase Intention. Whereas the Feel (Emotional Experience), Relate (Social Experience) variables also the Ease of Use, and Customer Trust variables have partial influence on Repurchase Intention, and there are influences between Customer Experience including Sense (Sensory Experience), Feel (Emotional Experience), Think (Cognitive Experience), Act (Physical Experience), Relate (Social Experience), Ease of Use, and Customer Trust for Repurchase Intention simultaneously.